Design Education Today Technical Contexts, Programs and Best Practices - Schaefer, Dirk; Coates, Graham; Eckert, Claudia (Springer International Publishing : Imprint: Springer, 2019)
This book provides extensive information on the key technical design disciplines, education programs, international best practices and modes of delivery that are aimed at preparing a trans-disciplinary design workforce for the future. It also presents a comprehensive overview of the scope of, and state of the art in, design education. The book highlights signature design education programs from around the globe and across all levels, in both traditional and distance learning settings. Additionally, it discusses professional societies for designers and design educators, as well as the current standards for professional registration, and program accreditation. Reflecting recent advances and emerging trends, it offers a valuable handbook for design practitioners and managers, curriculum designers and program leaders alike. It will also be of interest to students and academics looking to develop a career related to the more technical aspects of design. .